2010
DOI: 10.1002/bip.21365
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formation of the C‐terminal β‐hairpin of the B3 domain of the immunoglobulin‐binding protein G from Streptococcus. IV. Implication for the mechanism of folding of the parent protein

Abstract: A 34-residue α/β peptide, ], derived from the C-terminal part of the B3 domain of the immunoglobulin binding protein G from Streptoccocus was studied using CD and NMR spectroscopy at various temperatures, and by differential scanning calorimetry. It was found that the C-terminal part (a 16-residue-long fragment) of this peptide, which corresponds to the sequence of the β-hairpin in the native structure, forms structure similar to the β-hairpin only at T = 313 K, and the structure is stabilized by non-native lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 69 publications
5
41
0
Order By: Relevance
“…Using this approach, as the backbone H-bond interactions were defined solely as enthalpic constraints, our results show that backbone H-bonds only have a minor effect on the sigmoidal behavior (cooperative behavior) because of their small free energy contribution. This result is consistent with Scheraga and his coworkers, who pointed out that no clear evidence supports the presence of backbone H-bonds in non-turn regions [8,66,67,[80][81][82][83][84]. In other words, the backbone H-bond interaction may not contribute as much as expected in the cooperative formation of β-hairpins but may play only a structural as well as energetic constraint in modulation of the cooperative system [see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Using this approach, as the backbone H-bond interactions were defined solely as enthalpic constraints, our results show that backbone H-bonds only have a minor effect on the sigmoidal behavior (cooperative behavior) because of their small free energy contribution. This result is consistent with Scheraga and his coworkers, who pointed out that no clear evidence supports the presence of backbone H-bonds in non-turn regions [8,66,67,[80][81][82][83][84]. In other words, the backbone H-bond interaction may not contribute as much as expected in the cooperative formation of β-hairpins but may play only a structural as well as energetic constraint in modulation of the cooperative system [see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Work from the 90’s [1,3,4,8] as well as more recent studies [12,2329] showed that CD spectroscopy has very limited application in the investigation of the conformational dynamics of the β-hairpin-forming peptides. In the CD spectra of such investigated peptides, the signals corresponding to a turn or an extended conformation are usually very weak and cannot easily be distinguished from those corresponding to other structures such as α-helix or statistical coil [3,8,2327]. Adding structure-forcing solvents such us trifluoroethanol [3,8] or changing the temperature of the experiment [2327] does not provide useful information.…”
Section: Experimental Techniques Used To Determine Structure and Comentioning
confidence: 99%
“…Many groups also tried to modify the original G-hairpin peptide to study the influence of amino acid composition on the conformational dynamics and thermodynamic stability of the structure [10,1213,15,1827]. All of these studies have led to suggestions that there are four main factors that could contribute to the folding and stability of the G-hairpin: (1) the intrinsic β-turn properties of the residues which form a turn region [19,21,2327], (2) hydrophobic interactions between the side chains across the β-strands [12,20,2327], (3) interstrand hydrogen bonds that help define and maintain the architecture of the hairpin [15], and (4) polar side-chain-to-side-chain (sc-sc) interactions, including electrostatic interactions and salt bridges [10,13,18,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Karplus and co-workers 22 emphasized the dominant role of hydrophobic collapse of this part of the sequence. On the basis of our studies of the folding of the peptides excised from the C-terminal β-hairpin of the immunoglobulin binding protein (IGG1), 23À25 in our recent work 26 we concluded that the initial formation of chain reversals results from many interactions, in which the interplay between turn and hydrophobic-contact formation are of key importance. Additionally, from our studies of alaninebased peptides, 27,28 we concluded that the presence of charged groups (like or oppositely charged) on both ends of a short chain fragment might be another factor contributing to the formation of chain reversals because the charged groups could screen the nonpolar core from the solvent.…”
Section: Introductionmentioning
confidence: 97%